Mitigating peri-urban spatial challenges through the preservation of local identity a landscape development of Sta. Rita, Pampanga - Aloc, Albertene M. (College of Architecture, University of the Philippines Diliman, 2019)
Rapid outward development emerging from the urban core to the rest of the rural-urban region has resulted to complex landscapes on the fringe. Planning policies are prepared by areas located beyond the urban core in response to the social, economic, and physical change brought on by sprawl. Most existing strategies and tools utilized in urban development are grounded on the belief that the formation and transformation of a city can be controlled. Approaches such as Sta. Rita's multi-nodal spatial strategy aim to sort land uses to a specific, clearly classified and fixed category. However, these approaches fail to consider the dynamic characteristic of areas affected by, or are prone to the effects of peri-urbanization. In order to address the gap of Sta. Rita's spatial strategy, the proposed use of a rural-urban transect is put forward as a means of preserving local identity through the establishment of a transition zone between the emergent commercial center and the standing heritage center.